2021
DOI: 10.1101/2021.03.02.21252684
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-analytic findings on reading in children with cochlear implants

Abstract: This meta-analysis study aims to quantify the group differences in reading skills between children with cochlear implants and their hearing peers and between children with cochlear implants and children with hearing aids. Of the 5,642 articles screened, 47 articles met predetermined inclusion criteria. The robust variance estimation based meta-analysis models were used to synthesize all the effect sizes. Children with cochlear implants performed significantly worse than their hearing peers for phonological awa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 126 publications
0
2
0
Order By: Relevance
“…They demonstrated that each 1 °C rise was associated with a −4.8951% (t = −2.29, p = 0.0226) decrease in the number of daily cumulative confirmed cases of COVID-19. Similarly, Wang et al studied the effect of temperature on the number of confirmed cases in 429 cities in the world from 20 January 20 to 4 February 2020 [ 58 ]. The average, minimum, and maximum temperatures were 8.72 °C, 6.70 °C, and 12.42 °C, respectively.…”
Section: Meteorological Factorsmentioning
confidence: 99%
“…They demonstrated that each 1 °C rise was associated with a −4.8951% (t = −2.29, p = 0.0226) decrease in the number of daily cumulative confirmed cases of COVID-19. Similarly, Wang et al studied the effect of temperature on the number of confirmed cases in 429 cities in the world from 20 January 20 to 4 February 2020 [ 58 ]. The average, minimum, and maximum temperatures were 8.72 °C, 6.70 °C, and 12.42 °C, respectively.…”
Section: Meteorological Factorsmentioning
confidence: 99%
“…Since the spoken language and reading development in typically developing children is directly proportional, 3 Children with Cochlear Implant (CWCI) ought to benefit in their linguistic development post implantation as compared to the nonimplanted congenitally deaf population, as cochlear implants are known to provide better and more synchronised access to spoken language skills in implanted children. A review article 4 reported that the majority of children who are DHH (deaf or hard of hearing) develop spoken language successfully post cochlear implantation.…”
Section: Introductionmentioning
confidence: 99%